Safety and health management for highway operator in Klang Valley / Muhammad Ibnor Hanafi Jasmi - Hanafi Jasmi, Muhammad Ibnor (Faculty of Architecture, Planning and Surveying, 2013)
Highway maintenance is one of the important work that need to be carry out to ensure the highways user are not exposed to the risk of highways accidents. To determine the condition of the highway in a safe condition, highway operator are indirectly exposed to the risk of accidents on the highway. Case highway accidents among workers while doing maintenance work are very frequent, therefore this issue should be taken seriously before it becomes a major problem. The main purpose of this study is to identify the causes of the accident on the highway operators accident and improvement for highways safety and health management in order to reduce the risk of accidents to the highway operator, thus helping to increase the quality of the existing highway safety and health management. This study also will identify the awareness among highway maintenance operator towards safety and health. This study on the safety and health management has been carry out on three case study which is Guthrie Corridor Expressways (GCE), Kemuning-Shah Alam Highways (LKSA) and New Klang Valley Expressways (NKVE). Base on the selected case study PROPEL and PROLINTAS is the responsible party to manage on the highways maintenance All the information will be obtained from these two parties.